Health economics evidence for medical nutrition: are these interventions value for money in integrated care? - Walzer S; Droeschel D; Nuijten M; Chevrou-Séverac H (Dove Medical Press, 2014)
Stefan Walzer,1,2 Daniel Droeschel,1,3 Mark Nuijten,4 Hélène Chevrou-Séverac5 1MArS Market Access and Pricing Strategy GmbH, Weil am Rhein, Germany; 2State University Baden Wuerttemberg, Loerach, Germany; 3Riedlingen University, SRH FernHochschule, Riedlingen, Germany; 4Ars Accessus Medica BV, Jisp, Amsterdam, the Netherlands; 5Nestlé Health Science, Vevey, Switzerland Background: Health care decision-makers have begun to realize that medical nutrition plays an important role in the delivery of care, and it needs to be seen as a sole category within the overall health care reimbursement system to establish the value for money. Indeed, improving health through improving patients' nutrition may contribute to the cost-effectiveness and financial sustainability of health care systems. Medical nutrition is regulated by a specific bill either in Europe or in the United States, which offers specific legislations and guidelines (as provided to patients with special nutritional needs) and indications for nutritional support. Given that the efficacy of medical nutrition has been proven, one can wonder whether the heterogeneous nature of its coverage/reimbursement across countries might be due to the lack of health-related economic evidence or value-for-money of nutritional interventions. This paper aims to address this knowledge gap by performing a systematic literature review on health economics evidence regarding medical nutrition, and by summarizing the results of these publications related to the value for money of medical nutrition interventions. Methods: A systematic literature search was initiated and executed based on a predefined search protocol following the population, intervention, comparison, and outcomes (PICO) criteria. Following the systematic literature search of recently published literature on health economics evidence regarding medical nutrition, this study aims to summarize the results of those publications that are related to the value for money of medical nutrition interventions. The evaluations were conducted by analyzing different medical nutrition according to their indications, the economic methodology or perspective adopted, the cost source and utility measures, selected efficiency measures, as well as the incremental cost-effectiveness ratio. Results: A total of 225 abstracts were identified for the detailed review, and the data were entered into a data extraction sheet. For the abstracts that finally met the predefined inclusion criteria (n=53), full-text publications were obtained via PubMed, subito, or directly via each journal's Webpage for further assessment. After a detailed review of the full text articles, 34 publications have been qualified for a thorough data extraction procedure. When differentiating the resulting articles in terms of their settings, 20 studies covered inpatients, whereas 14 articles covered outpatients, including patients in community centers. When reviewing the value-for-money evaluations, the indications showed that the different results were mostly impacted by the different perspectives adopted and the comparisons that were made. In order to draw comprehensive conclusions, the results were split according to the main indications and diseases. Discussion: The systematic literature search has shown that there is not only an interest in health economics and its application in medical nutrition, but that there is a lot of ongoing research in this area. Based on the underlying systematic analysis, it has been shown that medical nutrition interventions offer value for money in the different health care settings, particularly for the specific disease areas that have been pointed out. Conclusion: Based on the systematic literature search that was performed, it was shown that medical nutrition interventions offer value for money in the different health care settings. Although medical nutrition has been the topic of some health economic analyses, the usual willingness to pay threshold used in health care rarely was applied. Often, these products are either directly part of a lump sum in the financing system (for example, diagnosis-related groups), or they are covered as out-of-pocket payments by patients directly. More research would be necessary to better understand how medical nutrition interventions can be optimally funded by the health care system, given the clinical value they bring to patients in their recovery process. Keywords: systematic review, medical nutrition, health economics